Interpreting evidence of differential item functioning (DIF) against learner responses: A South African example across three languages - Roux, Karen; van Staden, Surette (Journal for Language Teaching, 2025)
The aim of this study was to find evidence of differential item functioning (DIF) using an English, Afrikaans and isiZulu Grade 4 narrative text that was used during PIRLS 2016, followed by an investigation into learner responses to items that presented with DIF. One text that was used in PIRLS 2016, namely ‘The Pearl’ was used as an example here, where three out of 15 items presented with DIF across the three languages. Findings point to learners’ inability to respond to literal items, meaning those questions that do not require any inference making or evaluation at higher order levels of comprehension. Using a conceptual framework to establish linguistic, cultural, functional and metric equivalence, the current study provides evidence that there was no systematic bias. The current study presents results for a specific sub-set of qualitative analyses that was done during Phase II of a larger, mixed method study.